Report of Molluscs from Chimdi lake (Birju Tal), Sunsari district, Eastern Nepal - Surana, Ranjana; Subba, B.R.; Limbu, K.P. (Our Nature, 2006)
Molluscs from Chimdi lake have been reported. Ten species of Gastropod representing seven families and four species of bivalves representing two families are described here. Keywords: Molluscs, Chimdi lake, Sunsari doi:10.3126/on.v2i1.325 Our Nature (2004) 2:45-46